Preparation of Hierarchically Structured Amorphous Carbon Monoliths with Closed Spherical Mesopores via the Lower Critical Solution Temperature Phase Transition - Jeon, Seung-Yeol; Jeon, Hyeonyeol; Park, Tae Joon; Kang, Min Kwan; Cho, Byoung-Ki; Hwang, Seung Sang; Hur, Kahyun (WILEY-V C H VERLAG GMBH, 2019)
Some polymer mixture systems become immiscible above a specific temperature, the so-called lower critical solution temperature (LCST). In this work, the LCST behavior of a mixture of poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide) triblock copolymers and phenolic resin oligomers is observed, and the corresponding phase transition is exploited to develop a facile route to hierarchically structured carbon monoliths. Whereas evaporation-induced self-assembly generates hexagonal channels in the monoliths, an additional phase transition at the LCST leads to an ordered arrangement of isolated pores. The fabrication method involves annealing the gel-phased mixture with polymeric microbeads in a 3D-structured mold at the LCST, followed by thermosetting and a carbonization process. The LCST phase transition behavior is observed experimentally by in situ small-angle X-ray scattering, optical transparency measurements, differential scanning calorimetry, and infrared spectroscopy. The fundamental mechanism of the LCST phase transition is further investigated by atomistic molecular dynamics simulations.
Keywords: RESORCINOL-FORMALDEHYDE; BLOCK-COPOLYMERS; SILICA; SEPARATION; POLY(N-ISOPROPYLACRYLAMIDE); HYDROGELS; NETWORKS; PORES; RESIN; WATER